Effectiveness of Coping Strategies at Alleviating Cue-Induced Craving: a Pilot Study. (15th September 2014) - Dicker, Michelle; Frandsen, Mai; Palmer, Matthew A.; Ferguson, Stuart G.
Abstract : Introduction: Results from observational studies suggest that smoking-related cues play a role in triggering relapse. Coping strategies are among the most commonly used cessation strategies, but little is known about how they aid quitting. Aims: The aim of this pilot study was to evaluate the effect of a suite of selected coping techniques on alleviating cue-induced cravings. Methods: Thirty-seven daily smokers (Intervention: 20; Control: 17) participated in two laboratory cue-reactivity sessions, separated by approximately one week, during which craving was assessed before and after exposure to smoking-related cues. Following the first session, participants in the Intervention Group were taught a suite of coping strategies. During the second session, participants in the Intervention Group were encouraged to use these strategies. Results: Participants in the Intervention Group reported a slight decrease in craving following the acute exposure manipulation at the second session, compared to an increase in craving among participants in the Control Group. Intervention Group participants also reported a decrease in craving following prolonged exposure to the smoking cues (compared to an increase in craving among Control Group participants). In both cases, the difference between groups was more pronounced among smokers who responded to the cue-reactivity manipulation. The observed differences were not significant. Conclusions: The results of this pilot study suggest that coping techniques may be beneficial in alleviating both the initial spike in craving observed following acute cue exposure, and aid recovery during prolonged exposure. These findings need to be replicated in a larger study.